TINGKAT PENGETAHUAN DAN STIGMA TENTANG PENYAKIT HIV/AIDS DI REMAJA SMA - Juniwati Barus, Darwita; Henny Arwina Bangun; Sadestina Sembiring; Wilna Zaenab (Universitas Sari Mutiara Indonesia, 2025)
Knowledge about HIV/AIDS is considered important in the formation of stigma because it plays a role in correcting the wrong perceptions circulating in society including information about people who are at high risk of contracting HIV/AIDS, prevention of HIV/AIDS transmission, transmission mechanisms and what intermediaries can transmit HIV/AIDS. Knowledge about HIV/AIDS can be increased through information sources such as the role of health workers, the role of school education and the role of information media. HIV/AIDS (Human Immunodeficiency Virus/Acquired Immuno Deficiency Syndrome) stigma is part of the cognitive component of a person or community group that judges PLWHA (People with HIV/AIDS) negatively so that society takes a stance of rejection or discrimination against PLWHA. The stigma of PLWHA can be seen from the poor mindset of society that avoids sufferers due to excessive fear and unfair treatment of PLWHA. Lack of understanding of HIV/AIDS knowledge is the main cause of the formation of this stigma in society. Knowledge about HIV/AIDS (Human Immunodeficiency Virus/Acquired Immuno Deficiency Syndrome) is one of the factors that play a role in the formation of stigma towards HIV/AIDS. This study aims to determine the relationship between the level of knowledge about HIV/AIDS and the stigma of HIV/AIDS in high school students. This study is a descriptive study. The measuring instrument used was a closed questionnaire to obtain data in the form of knowledge and stigma values ​​that have been categorized in 60 grade XI students of SMA Negeri 17 Medan. The results of the study found that the level of knowledge in the low category was owned by 10 students (16.7%), sufficient 9 students (15%), good 41 students (68.3%) and high stigma category was owned by 4 students (6.7%), moderate 32 students (53.3%), low 24 students (40%).